Corporate culture, team culture : removing the hidden barriers to team success - Sherriton, Jacalyn Carol (Amacom, 1997)
"Corporate Culture/Team Culture is the first book to address in depth the issue of changing the organizational culture to support team effectiveness. It also presents a practical, proven model for achieving such transformation, and illustrates the process with three extended case studies and numerous additional examples of the model in action." "To create high-performing teams, the authors say, we must first acknowledge that teamwork doesn't come naturally. While individuals and organizations are trained to pay lip service to the value of working together, this approach actually clashes with cultures that reward "looking out for number 1." Add in the turf battles that still smolder in most workplaces - especially in companies that have recently merged or downsized - and teams can become powder kegs." "Yet, as the book's examples reveal, teaming is a vital way to structure work and meet today's business challenges. Whether your organization is fine-tuning its team efforts or just starting out, Corporate Culture/Team Culture shows you how to succeed by tackling cultural issues from the ground up."--Jacket.